Care of older people and people requiring palliative care with COVID‐19: guidance from the Australian National COVID‐19 Clinical Evidence Taskforce. Issue 4 (5th December 2021) - Cheyne, Saskia; Lindley, Richard I; Smallwood, Natasha; Tendal, Britta; Chapman, Michael; Fraile Navarro, David; Good, Phillip D; Jenkin, Peter; McDonald, Steve; Morgan, Deidre; Murano, Melissa; Millard, Tanya; et al.
Abstract: Introduction: Older people living with frailty and/or cognitive impairment who have coronavirus disease 2019 (COVID‐19) experience higher rates of critical illness. There are also people who become critically ill with COVID‐19 for whom a decision is made to take a palliative approach to their care. The need for clinical guidance in these two populations resulted in the formation of the Care of Older People and Palliative Care Panel of the National COVID‐19 Clinical Evidence Taskforce in June 2020. This specialist panel consists of nursing, medical, pharmacy and allied health experts in geriatrics and palliative care from across Australia. Main recommendations: The panel was tasked with developing two clinical flow charts for the management of people with COVID‐19 who are i) older and living with frailty and/or cognitive impairment, and ii) receiving palliative care for COVID‐19 or other underlying illnesses. The flow charts focus on goals of care, communication, medication management, escalation of care, active disease‐directed care, and managing symptoms such as delirium, anxiety, agitation, breathlessness or cough. The Taskforce also developed living guideline recommendations for the care of adults with COVID‐19, including a commentary to discuss special considerations when caring for older people and those requiring palliative care. Changes in management as result of the guideline: The practice points in the flow charts emphasise quality clinical care, with a focus on addressing the most important challenges when caring for older individuals and people with COVID‐19 requiring palliative care. The adult recommendations contain additional considerations for the care of older people and those requiring palliative care.